Laparoscopic ovarian tissue collection for fertility preservation in children with malignancies: a multicentric experience - Perelli, Federica; Fusi, Giulia; Lonati, Luca; Gargano, Tommaso; Maffi, Michela; Avanzini, Stefano; Palo, Federico; Blanco Verdú, Maria Dolores; Del Cañizo López, Agustín; Garrido Colino, Carmen; Perucca, Giulia; Mattioli, Girolamo; et al. (Frontiers in Surgery, 2024)
Long survivors after childhood cancer are increasing thanks to oncological improvements. Their quality of life and fertility-sparing should be considered in the early phases of each oncological pathway. Cryopreservation of ovarian tissue removed before starting gonadotoxic therapies is the only fertility-sparing procedure available for prepubertal children affected by cancer and it does not affect the timing of the start of the treatment. The present study shows the surgical and clinical outcomes following laparoscopic ovarian tissue collection (LOTC) for a total of 311 patients aged between 0 and 17 years old from four different European Centers. Only two major complications